Gliamimic: a longitudinal, multimodal in vitro platform for evaluating glioblastoma treatment response and post-treatment tumor progression in patient-derived organoids or spheroids - Selina Camenisch; Luisa Bell; Nadine Stokar-Regenscheit; Natalia Vélez Char; Wolfram Jochum; Simon Heinze; Anna Maria Zeitlberger; Thomas Hundsberger; Marian Neidert; Peter Wick; Vanesa Ayala-Nunez (Journal of Experimental & Clinical Cancer Research, 2026)
Abstract Treatment resistance and recurrence continue to define the clinical landscape of glioblastoma (GBM), yet their study is limited by traditional in vitro frameworks that fail to capture long-term treatment dynamics and tumor evolution. Here we present GliaMimic, a longitudinal in vitro platform incorporating irradiation and multi-dose temozolomide (TMZ). Using patient-derived organoids (PDOs) and cell line-derived spheroids, tumor progression and treatment response were monitored non-invasively over four weeks. Substantial declines in metabolic activity and viability at clinically relevant TMZ concentrations (≤ 10 µM) emerge only after prolonged exposure, whereas short-term assays captured effects only at supraphysiological doses. Notably, PDOs, patient-derived spheroids, and their cell line-derived counterparts exhibited distinct patterns of treatment response and tumor progression, underscoring the importance of model selection in preclinical studies. Following treatment cessation, the platform captured distinct, patient-specific post-treatment tumor behaviors with persistent viable and metabolically active populations across all models with more pronounced changes in PDOs. By moving beyond static molecular diagnostics, GliaMimic provides a longitudinal in vitro treatment evaluation platform for preclinical testing.